2011
DOI: 10.1016/j.envpol.2011.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Blood dynamics of mercury and selenium in northern elephant seals during the lactation period

Abstract: a b s t r a c tThe effects of reproduction and maternal investment (i.e., milk transfer) on trace element levels remain poorly understood in marine mammals. We examined the blood dynamics of mercury (Hg) and selenium (Se) during lactation in the northern elephant seal (Mirounga angustirostris), a top predator from the North Pacific Ocean. Total Hg and Se levels were measured in whole blood and milk of 10 motherepup pairs on days 5 and 22 of lactation. Both Hg and Se were transferred to offspring through the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 57 publications
3
40
1
Order By: Relevance
“…Therefore, an increase of hemoglobin concentration contributes to the increase of Fe and Hg levels in the blood. Interestingly, blood concentrations of Hg, Se, and Cu in weaned pups of the present study were totally in continuity with those previously determined in northern elephant seal suckling pups [13]. Values in the early postweaning fast were very close to values in late lactation (respectively, 0.066 and 0.077 mg/kg wet wt for Hg, 1.5 and 1.3 mg/kg wet wt for Se, and 0.98 and 0.93 mg/kg for Cu) in following the increasing or decreasing trend observed during lactation (Fig.…”
Section: Changes In Blood Concentrationssupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, an increase of hemoglobin concentration contributes to the increase of Fe and Hg levels in the blood. Interestingly, blood concentrations of Hg, Se, and Cu in weaned pups of the present study were totally in continuity with those previously determined in northern elephant seal suckling pups [13]. Values in the early postweaning fast were very close to values in late lactation (respectively, 0.066 and 0.077 mg/kg wet wt for Hg, 1.5 and 1.3 mg/kg wet wt for Se, and 0.98 and 0.93 mg/kg for Cu) in following the increasing or decreasing trend observed during lactation (Fig.…”
Section: Changes In Blood Concentrationssupporting
confidence: 77%
“…Only levels of Hg and Se were analyzed in northern elephant seal females and their pups during lactation (reaching 0.3 and 1.1 mg/kg wet wt, respectively, in blood of females from early lactation [13]). That study showed that fasting associated with milk production in lactating females, as well as suckling in pups, induced rapidly significant changes in Hg and Se blood levels over the lactation period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the annual moult, female elephant seals return to the ocean for the long foraging trip, at which time gestation occurs. Maternal offloading of methylmercury in marine mammals occurs mostly via the placenta during gestation and to a much lesser extent during lactation [50,51]. For elephant seals arriving from the short foraging trip, there has been no recent maternal transfer of methylmercury and the greatest amount of time has elapsed since the prior moult ( figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the increased mass and body condition (i.e. growth dilution effect due to increase in body mass) of seals at the end of the long foraging trip, in preparation for the extended lactation and fasting period associated with breeding, probably reduces mercury concentrations in internal tissues because changes in body condition can influence mercury concentrations in vertebrates [51,52]. Thus, the higher mercury concentrations we observed in seal blood and muscle after the short foraging trip (about 150 days shorter than the long foraging trip) were probably caused by decreased body mass (mass approx.…”
Section: Discussionmentioning
confidence: 99%